Analisis Likuiditas Bank Umum Syariah dengan Pendekatan Autoregressive Distributed Lag (ARDL) - Bintang Putri Pertiwi; Heri Sudarsono (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
This study aims to determine the influence of internal and external factors on the liquidity of Islamic banks. The research observation period was from January 2015 to April 2019 using the autoregressive distributed lag (ARDL) data processing method. ARDL is used to determine the short-term and long-term independent variables on the liquidity variable. The results of data processing found that CAR has a significant negative effect on FDR, but it is not significant in the short term. Likewise, ROA has a significant positive effect on FDR only in the long term. NPF in the short and long term has a significant negative effect on FDR. Then BOPO has a significant positive effect on FDR only in the long term. The BI Rate has a short-term and long-term effect on FDR, but in the short term, the BI Rate has a significant positive effect, while in the long term, the BI Rate has a significant negative effect on FDR. Inflation has a negative effect but does not significantly affect FDR in the long and short term. IPI in the long and short term has a significant positive effect on FDR.